The relationship between transformational leadership practiced and the level of job satisfaction among lecturers in MARA professional college, Malaysia / Fareez Ashraf Mahzan and Norazah Mohd. Nordin - Mahzan, Fareez Ashraf; Mohd. Nordin, Norazah (Universiti Teknologi MARA, 2021)
The quality and level of job satisfaction among lecturers play a significant role in implementing transformation to improve the education system. The main reason for the decreasing of job performances among lecturers is due to the low level of job satisfaction. This study aimed to examine the relationship between a director's transformational leadership style and the level of job satisfaction among lecturers at MARA Professional College. This is a survey study employing descriptive and inferential quantitative method. The Multi factor Leadership Questionnaire (MLQ) and Job Descriptive Index (JDI) instruments were distributed to 64 participants that were chosen using simple random sampling from the 75 population of MARA Professional College lecturers. The data was analyzed using Statistical Package for Social Science (SPSS) version 22. The findings revealed that the level of practice of the director on transformational leadership was low. In addition, there was a significant relationship between the transformation leadership practice of the director and the level of job satisfaction among lecturers at MARA Professional College. The level of job satisfaction among the lecturers was influenced by the director's leadership practice, thus a director can increase the level of job satisfaction among the staff by practicing the transformational leadership style in managing a college. The findings are expected to assist the organization of MARA Professional College to identify the level of work pressure faced by the lecturers.